2020
DOI: 10.37500/ijessr.2020.3014
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Understanding of Indonesian History and the Nationalism Attitude of State Senior High School Students

Abstract: This study aims to determine the relationship of understanding Indonesian history with the nationalism attitude of students of State Senior High Schools in Ngaglik District, Yogyakarta. This research is a type of correlational research that uses a quantitative approach. The research sample were 126 students, data collection using tests and questionnaires. Tests are used to reveal data about understanding Indonesian history, while questionnaires are used to reveal nationalism. The validity test of the instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Indonesian history lessons that implements the values of national insight in Indonesian history learning materials are very important to instill nationalism and state attitudes (Banks, 2017;Sudiatmi, 2019), which contains the values of accepting and diversity, tolerance, integrity and national unity, and fostering awareness for the crisis of solidarity due to Indonesia's pluralism (Matsaganis, 2011). These values are part of the national outlook (Davis, 2003;Wibowo, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indonesian history lessons that implements the values of national insight in Indonesian history learning materials are very important to instill nationalism and state attitudes (Banks, 2017;Sudiatmi, 2019), which contains the values of accepting and diversity, tolerance, integrity and national unity, and fostering awareness for the crisis of solidarity due to Indonesia's pluralism (Matsaganis, 2011). These values are part of the national outlook (Davis, 2003;Wibowo, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the attitude of nationalism focused on the ability to explain historical values [24], aspects of cultural diversity [25], and interest in learning history [26]. This study focused on examining the relationship between understanding Indonesian history, multiculturalism, and historical awareness with students' nationalistic attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Many foreign cultures that have entered not only can weaken the national identity but also these can make students to be a lazier in studying. Wibowo, Wulandari, and Setiawan [7], revealed that most of students are lazy to study and know related to something beneficial knowledge such as historical values. As a consequence, they do not understand and aware about their historical nation [8], [9].…”
Section: Introductionmentioning
confidence: 99%